Optimizing MSME Profits using the Simplex Method - Alan Rusdiana; Budi Rusdian; Ajeng Siti Nurkolbu; Alfira Hasna Adkhilni; Tria Waliatul Maola (Finance and Business Management Journal, 2024)
This research aims to calculate the maximum profit from selling spinach chips, onion cakes and steak cakes at Guna Asih MSMEs and to determine the use of the simplex method for raw material constraints faced by Guna Asih MSMEs. In addition, this research uses POM-QM for Windows software to estimate the maximum profit obtained from each production of spinach chips, onion cakes and sistik cakes at Guna Asih UMKM so as to have an accurate estimate. This research method involves problem identification, selection of problem-solving models, data collection, data processing and analysis, model implementation, and evaluation of results. The research results show that the simplex method can be used to determine maximum profits in Guna Asih MSMEs. The maximum profit obtained by MSMEs is IDR. 1,277,778 per day when only producing spinach chips (X1) 1.12 times more than previous production or 336 pcs and producing onion cakes (X2) 5 times more than previous production or 500 pcs. This profit is greater than the profit before optimization which only earned IDR. 900,000 from 300 pcs of spinach chips, 100 pcs of onion cakes and 60 pcs of steak cakes. Apart from that, the use of POM-QM for Windows software is very relevant in solving linear programming problems using the simplex method because it can help in completing maximum profit level calculations quickly, precisely and accurately.